1994
DOI: 10.1080/10401339409539653
|View full text |Cite
|
Sign up to set email alerts
|

Tutor evaluation of problem-based learning in behavioral sciences courses

Abstract: To cite this article: David T. A. Vernon (1994) Tutor evaluation of problem-based learning in behavioral sciences courses, Teaching and Learning in Medicine, 6:2, 91-95To link to this article: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A few studies have concluded that faculties are generally satisfied with PBL (Vernon 1994, 1995). A recent study of 30 tutors in three behavioural science courses concluded that ratings by teaching staff significantly favoured PBL over traditional methods (Vernon 1994). A more recent study by the same author surveyed more than 1200 tutors at 22 medical schools across North America (Vernon 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have concluded that faculties are generally satisfied with PBL (Vernon 1994, 1995). A recent study of 30 tutors in three behavioural science courses concluded that ratings by teaching staff significantly favoured PBL over traditional methods (Vernon 1994). A more recent study by the same author surveyed more than 1200 tutors at 22 medical schools across North America (Vernon 1995).…”
Section: Introductionmentioning
confidence: 99%